Comparative genome analysis of VSP-II and SNPs reveals heterogenic variation in contemporary strains of Vibrio cholerae O1 isolated from cholera patients in Kolkata, India. - Daisuke Imamura; Masatomo Morita; Tsuyoshi Sekizuka; Tamaki Mizuno; Taichiro Takemura; Tetsu Yamashiro; Goutam Chowdhury; Gururaja P Pazhani; Asish K Mukhopadhyay; Thandavarayan Ramamurthy; Shin-Ichi Miyoshi; Makoto Kuroda; et al. (PLOS Neglected Tropical Diseases, 2017)
Cholera is an acute diarrheal disease and a major public health problem in many developing countries in Asia, Africa, and Latin America. Since the Bay of Bengal is considered the epicenter for the seventh cholera pandemic, it is important to understand the genetic dynamism of Vibrio cholerae from Kolkata, as a representative of the Bengal region. We analyzed whole genome sequence data of V. cholerae O1 isolated from cholera patients in Kolkata, India, from 2007 to 2014 and identified the heterogeneous genomic region in these strains. In addition, we carried out a phylogenetic analysis based on the whole genome single nucleotide polymorphisms to determine the genetic lineage of strains in Kolkata. This analysis revealed the heterogeneity of the Vibrio seventh pandemic island (VSP)-II in Kolkata strains. The ctxB genotype was also heterogeneous and was highly related to VSP-II types. In addition, phylogenetic analysis revealed the shifts in predominant strains in Kolkata. Two distinct lineages, 1 and 2, were found between 2007 and 2010. However, the proportion changed markedly in 2010 and lineage 2 strains were predominant thereafter. Lineage 2 can be divided into four sublineages, I, II, III and IV. The results of this study indicate that lineages 1 and 2-I were concurrently prevalent between 2007 and 2009, and lineage 2-III observed in 2010, followed by the predominance of lineage 2-IV in 2011 and continued until 2014. Our findings demonstrate that the epidemic of cholera in Kolkata was caused by several distinct strains that have been constantly changing within the genetic lineages of V. cholerae O1 in recent years.